2009
DOI: 10.5026/jgeography.118.776
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Stratigraphic Distribution Analysis of Methane-hydrate-bearing Submarine-fan Turbidite Sandstones in the Eastern Nankai Trough Area: Relationship between Turbidite Facies Distributions and BSR Occurrence

Abstract: Since previous research revealed that most of the methane hydrates in the eastern Nankai Trough area occur in matrix pores of turbidite sandstones, the facies distribution of turbidite sandstones may be one of the important keys to evaluate the distributions and actual volume of methane hydrates in the eastern Nankai Trough area. This paper attempts to reconstruct depositional processes of submarine-fan turbidites, and examines the relationship between turbidite facies distributions and bottom simulating refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 18 publications
(2 reference statements)
0
41
0
Order By: Relevance
“…1) (e.g., Baba and Yamada, 2004;Takano et al, 2009Takano et al, , 2013. The results of the ODP and IODP operation revealed that these basins are filled with submarine turbiditic sediments, which are commonly rich in quartz and feldspar (Underwood et al, 2005;Kinoshita et al, 2009).…”
Section: Geological Backgroundmentioning
confidence: 94%
See 2 more Smart Citations
“…1) (e.g., Baba and Yamada, 2004;Takano et al, 2009Takano et al, , 2013. The results of the ODP and IODP operation revealed that these basins are filled with submarine turbiditic sediments, which are commonly rich in quartz and feldspar (Underwood et al, 2005;Kinoshita et al, 2009).…”
Section: Geological Backgroundmentioning
confidence: 94%
“…The targeted basin fills, the Pleistocene Ogasa Group, cover the northern flank of the Daini Atsumi Knoll east of the Kumano forearc basin, and consist of confined deepwater turbidite system (Egawa et al, 2013;Noguchi et al, 2011;Takano et al, 2009). Seismic stratigraphy of this Ogasa turbidite system is subdivided into nine sequences from Og-a to Og-i in ascending order , among which sequence Og-b is defined as the gas hydrate reservoir sequence in the study area (Noguchi et al, 2011;Komatsu et al, 2015).…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of active faults have been recognized by the KAIKO-Tokai survey (the Research Group for Active Submarine Faults off Tokai, 1999;Soh and Tokuyama, 2002). The stratigraphy of the forearc basin of the eastern Nankai Trough is comprised of the Plio-Pleistocene Kakegawa and Ogasa Groups (Hiroki et al, 2004;Arai et al, 2006;Takano et al, 2008Takano et al, , 2009). Takano et al (2008Takano et al ( , 2009) conducted a seismicsequence stratigraphic analysis using 2-D/3-D seismic surveys and well data (including cores and logs) to reconstruct the depositional processes of submarine-fan turbidites in the eastern Nankai Trough area.…”
Section: The Geological Setting Of the Eastern Nankai Troughmentioning
confidence: 98%
“…The eastern part of the arc was under a continued compressive regime, which provoked formation of a regional unconformity in the eastern forearc around 3.0~2.5 Ma (e.g., Kameo et al 2010;Kameo and Sekine 2013). Watershed mountains simultaneously emerged along the MTL in the central part of SWJ (Oka 1978;Oka and Sangawa 1981;Mizuno 1987), which was succeeded by extensive deformation of the adjoining forearc basin (Takano et al 2009). As depicted in the isochron map of the yellow horizon (Figure 6), the tension graben around Beppu Bay in the western part of the island arc became inactive and the basin architecture changed to be under a transtensional/transpressional regime.…”
Section: Expansion Of the Contractional Domain (3~1 Ma)mentioning
confidence: 99%